2018
DOI: 10.1016/j.pec.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Nudging in screening: Literature review and ethical guidance

Abstract: Four specific recommendations follow from the review and the analysis: 1) Nudging should be addressed in an explicit and transparent manner. 2) The means of nudging have to be in proportion to the benefit-harm ratio. 3) Disagreement on the evidence for either benefits or harms warrants special care. 4) Assessing and assuring the intended outcome of nudging appears to be crucial, as it can be context dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 114 publications
1
29
0
Order By: Relevance
“…Additionally, we also used this question to gain a better understanding of how this nudge would facilitate or undermine people’s ability to make an informed choice about screening. Nudge type interventions such as social norms interventions have been criticized in terms of informed decision making [2729]. As interventions should avoid being manipulative or paternalistic to enable people to make an informed choice based on knowledge of the harms and benefits of cancer screening, it is important to know whether nudges influence information seeking behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we also used this question to gain a better understanding of how this nudge would facilitate or undermine people’s ability to make an informed choice about screening. Nudge type interventions such as social norms interventions have been criticized in terms of informed decision making [2729]. As interventions should avoid being manipulative or paternalistic to enable people to make an informed choice based on knowledge of the harms and benefits of cancer screening, it is important to know whether nudges influence information seeking behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Written information is generally the main or only way that invitees learn about screening in organised programmes. 6,7 However, there may be opportunities to increase perceived acceptability of reduced-frequency risk-stratified breast screening, using subtle methods of designing information that still respect these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that preferences and perceptions can be influenced using a wide range of psychological methods, and in diverse healthcare contexts and clinical groups. 8 Authors of screening information materials necessarily decide whether to summarize benefits of screening before risks, or vice versa, 6 and this order may have psychological effects. 8 A study of genetic testing for breast cancer risk found that participants had more positive attitudes and intentions (but greater risk perceptions and fewer disadvantages) when advantages were presented before disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…As we have seen, the issue of informing about screening touches on general debates on irrational aspects of decision-making, 93 cognitive and affective biases and heuristics, 94 and free will. It has also been argued that nudging can be acceptable 95 and even commendable for some types of screening 96 (although not for mammographic screening).…”
Section: Framing Bias and The Informed Choice Modelmentioning
confidence: 99%